2015
DOI: 10.1371/journal.pone.0121225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Expression Level of O6-Alkylguanine-DNA Alkyltransferase on the Formation of DNA Interstrand Crosslinks Induced by Chloroethylnitrosoureas in Cells: A Quantitation Using High-Performance Liquid Chromatography-Mass Spectrometry

Abstract: Chloroethylnitrosoureas (CENUs), which are bifunctional alkylating agents widely used in the clinical treatment of cancer, exert anticancer activity by inducing crosslink within a guanine-cytosine DNA base pair. However, the formation of dG-dC crosslinks can be prevented by O6-alkylguanine-DNA alkyltransferase (AGT), ultimately leading to drug resistance. Therefore, the level of AGT expression is related to the formation of dG-dC crosslinks and the sensitivity of cells to CENUs. In this work, we determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…However, AGT protein was able to mediate direct repair by transferring the chloroethyl group in O 6 -chloroethylation, an intermediate product in the procedure of ICL formation, to forestall the ICLs generation. , Therefore, SF-767 cells with low AGT activity were observed to have higher levels of ICLs after CENU exposure, whereas SF-763 cells with high AGT expression exhibited lower cross-linking levels. Moreover, the high AGT activity appeared to correlate well with the elevated cell resistance to chloroethylating agents, which were also in good agreement with the obtained results that low AGT level potentiated the loss of cellular viability in human glioma cell lines. , Similar results were also obtained in previous studies. Bodell and colleagues quantified seven DNA alkylation products formed in different human glioma cell lines treated with CENU. , DNA ICLs were proved to have the potential to be used as molecular dosimeters of therapeutic response.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, AGT protein was able to mediate direct repair by transferring the chloroethyl group in O 6 -chloroethylation, an intermediate product in the procedure of ICL formation, to forestall the ICLs generation. , Therefore, SF-767 cells with low AGT activity were observed to have higher levels of ICLs after CENU exposure, whereas SF-763 cells with high AGT expression exhibited lower cross-linking levels. Moreover, the high AGT activity appeared to correlate well with the elevated cell resistance to chloroethylating agents, which were also in good agreement with the obtained results that low AGT level potentiated the loss of cellular viability in human glioma cell lines. , Similar results were also obtained in previous studies. Bodell and colleagues quantified seven DNA alkylation products formed in different human glioma cell lines treated with CENU. , DNA ICLs were proved to have the potential to be used as molecular dosimeters of therapeutic response.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Besides, it was obviously seen that the survival rate of SF-763 cells were slightly higher than SF-767 under the same conditions. Similar results were obtained by using trypan blue exclusion assay in our previous study, and higher O 6 -alkylguanine-DNA alkyltransferase (AGT) expression in cells was demonstrated to be related with higher cell resistance to ACNU. , On the basis of these results, it was clear that high expression of AGT repair protein is a crucial factor for low cytotoxicity, which leads to cell resistance to chloroethylating agents …”
Section: Results and Discussionsupporting
confidence: 86%
“…O 6 -alkylguanine-DNA alkyltransferase (AGT), also known as O 6 -methylguanine-DNA methyltransferase (MGMT), plays an important role in drug resistance to CENUs. Previous studies revealed that AGT provided a unique DNA repair means by transferring the lesion located at the O 6 position of guanine to Cys145 in an irreversible stoichiometric suicidal reaction. , Although this repair protects normal cells from mutagenic and carcinogenic effects by repairing the O 6 -alkylguanine lesions, it induces drug resistance to certain alkylating agents, such as CENUs, used as cancer chemotherapy. , Several investigations documented that the drug resistance to CENUs were greatly correlated with the contents of AGT in cancer cells. , As mentioned above, dG-dC cross-link, the most cytotoxic lesion induced by CENUs, is formed from the O 6 -alkylation of guanine. However, the ability of AGT to repair O 6 -alkylguanine and thus prevent the formation of dG-dC cross-link renders AGT the main culprit in promoting resistance of cancer cells to CENUs.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Several investigations documented that the drug resistance to CENUs were greatly correlated with the contents of AGT in cancer cells. 14,15 As mentioned above, dG-dC cross-link, the most cytotoxic lesion induced by CENUs, is formed from the O 6 -alkylation of guanine. However, the ability of AGT to repair O 6 -alkylguanine and thus prevent the formation of dG-dC cross-link renders AGT the main culprit in promoting resistance of cancer cells to CENUs.…”
Section: Introductionmentioning
confidence: 99%
“…However, ICLs might trigger not only cytotoxicity, but also genotoxicity, leading to tumor formation as a side effect of the chemotherapeutic treatment [5, 11, 12]. The involvement of O 6 -alkylguanine-DNA alkyltransferase (AGT) in the repair of chloroethylating guanine has been widely reported [6, 13–15]. Recently, the mechanism of ICL-repair as well as the cytotoxic effects of ICLs has been slightly clarified [11].…”
Section: Introductionmentioning
confidence: 99%